Comportamiento, uso e higiene en pacientes portadores de prótesis bucales. Unidad de Atención Odontológica UNACH - Jael Stephanie, Carlosama Heredia (2021)
The main objective of the present study was to evaluate the behavior, use and hygiene in patients wearing oral prostheses treated at the UNACH's Dental Care Unit. The research had a mixed approach, transversal, observational, exploratory and descriptive cohort. The type of sample was non-probabilistic. Eighty-one patients were chosen for convenience, who signed the informed consent and carried out a survey validated by construct. Data processing showed a predominance of male sex, with an average age of 58.8 years. A greater recurrence of prosthesis in the upper arcade is reported; the condition of the prosthesis is proved to be related to years of use, and good food chewing efficacy was indicated based on the type. Before the mismatch of the prosthesis is reported an immediate visit to the dentist is needed. It may indicate that if no damage occurs in the oral cavity, the patient continues to use the prosthesis. Most patients report the non-removal of the prosthesis at any time. The majority of patients receive hygiene instructions and also go to subsequent controls when they have discomfort. They comment to clean the prosthetic device twice a day and do not know of any disinfectant substances. Then, 74% of the patients behave negatively towards the use, and 70% about the hygiene. There is a relationship between use and hygiene behavior with the prosthetic condition (p=0.05; p=0.038), and use behavior and years (p=0.00).